Gender Diversity Towards Investment Decision For Retirement Preparation - Agus Zainul Arifin (Jurnal Manajemen, 2019)
The aim of this paper is to examine influence of the relationship between Financial Behavior on Investment decision that moderated Retirement variable of employees who live in DKI Jakarta area in 2018 This study approach is survey research by distributing questionnaires online and manually. Data analysis was carried out using path analysis, namely by testing the outer and inner models. Results indicate that Financial behavior affects Retirement planning and investment decisions. Second, Retirement preparation does not affect investment decisions. Third,Â  Retirement planning is not a moderation variable of the relationship between financial behavior and investment decisions,Â  both for male, female, and overall gender. Gender factor does not has different effect relationship between Financial Behavior on Investment decision and retirement preparation.